Sociology : - Schaefer, Richard T. (McGraw-Hill, 2013)
Sociology A Brief Introduction make sure students come prepared to class by assigning our many e-book activities; Unique to this program Sociology A Brief Introduction encourages students to take sociology with them in their everyday lives just as Rick keeps a small notebook of daily sociological events; In Sociology brief instructors get the most trusted content in manageable form; This coupled with powerful digital learning tools makes Sociology brief an ideal choice for your introductory course